Pendampingan Sertifikasi Produk Halal UMKM Keripik Sambal Siti Boru Regar Padangsidimpuan - Nurhotia Harahap; Darania Anisa; Nada Putri Rohana; Iklima Lubis; Sintia Apriani; Sofyan Hanafi Lubis (JURNAL PENGABDIAN KADER BANGSA, 2025)
Assistance with halal product certification is a service activity that aims to help business actors obtain halal certificates for the products they produce. The research was carried out by assisting MSMEs with "Siti Boru Regar" chili chips in Padangsidimpuan, North Sumatra. The method of this activity is PAR (Participatory Action Research). Assistance is carried out by training Sambal Chips MSME actors in filling out the SJPH manual, filling out the SiHalal application and inputting production data into the SiHalal application, as well as carrying out halal verification for the Salam Chips MSME actors who are accompanied. Assistance is provided until Sambal Chips MSMEs get Halal certificates for free. So the result of this service is the certification of halal products for the accompanied Sambal Chips MSMEs, which is expected to provide added value to the products produced so that public/buyer confidence becomes more confident in the halalness of the products produced, and is expected to increase sales results for Sambal Chips MSMEs "Siti Boru Regar" Padangsidimpuan.